Evaluation of the recurrence rate of breast cancer after surgery in tertiary hospital from the Federal District - Vivan, Thais Karla; Santana, Vinicius Xavier de; Passos, Mauro Pinto; Souza, Karoline Evangelista de; Magalhaes, Mayra Teixeira (Mastology, 2026)
Objective: To evaluate recurrences related to breast surgery for adenectomy in the mastology sector of the tertiary hospital in the Federal District, from June 2013 to June 2020. Methods: This is an observational, descriptive, retrospective study with data collection from selected patient records. Results: Sixty-one patients who underwent adenectomy were considered; four were excluded because they did not meet the inclusion criteria. The most common age groups were between 50–59 years (35.1%), followed by 40–49 years (26.3%), and 30–39 years (19.3%). The most common body mass index among patients was between 20–25 kg/m2. In the group of patients who underwent the procedure and had recurrence, the average age was 39.3 years. Of the 57 patients evaluated in the study, six presented recurrence: one (1.8%) presented local, one (1.8%) patient had recurrence in the NAC, two (3.5%) had local + regional recurrence, and two (3.5%) presented distant metastasis. Pre-menopause (50%) was the most frequent status in the recurrence group. Ductal histological type was related to all cases of recurrence. T1c and T3 and histological grade II were the prevalent characteristics. The tumor subtypes luminal B (ki-67>14; 50%) and luminal B with human epidermal growth factor receptor-type 2-positive (HER2+) (ki67>15%; 33.3%) were the predominant subtypes. The most frequent reason for adenectomy was multicentric/multifocal disease (33.3%), the majority, radiated in the lateral upper quadrant (66.7%), was the type of incision related to recurrence. Conclusion: Adenectomy offers comprehensive treatment of breast injuries, with favorable aesthetic outcomes. The overall recurrence rate in the present study was 9.5%. The local recurrence rate was 1.8%, which is consistent with those found in the literature, e.g., with rates of 1.6% and 2.9% after 5 years of study.